2014
DOI: 10.4314/thrb.v15i4.2
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of outcome among patients with obstructive jaundice at Bugando Medical Centre in north-western Tanzania

Abstract: Despite recent advances both in preoperative diagnosis and postoperative care, obstructive jaundice still contributes significantly to high morbidity and mortality. A prospective study was undertaken to identify predictors of outcome among patients with obstructive jaundice at Bugando Medical Centre in north-western Tanzania. A total of 138 patients were studied. The male to female ratio was 1:1.6. The median age of patients was 58 years. Patients with malignant obstructive jaundice were older than those of be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 9 publications
3
11
0
1
Order By: Relevance
“…Biliary stones were the most common cause of biliary obstruction among the age group of 36–50 years with predilection for male gender in this study. However the prevalence was more in females in other studies in Ethiopia, Tanzania, Italy, and the USA 7 , 17–19 . Estrogen causes super-saturation of biliary cholesterol due to hepatic hypersecretion, potentiating nucleation of cholesterol monohydrate crystals.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Biliary stones were the most common cause of biliary obstruction among the age group of 36–50 years with predilection for male gender in this study. However the prevalence was more in females in other studies in Ethiopia, Tanzania, Italy, and the USA 7 , 17–19 . Estrogen causes super-saturation of biliary cholesterol due to hepatic hypersecretion, potentiating nucleation of cholesterol monohydrate crystals.…”
Section: Discussionmentioning
confidence: 54%
“…Predictors of poor outcome are long duration of jaundice, malignant causes, and high bilirubin levels. 7 …”
Section: Introductionmentioning
confidence: 99%
“…This study showed that bulk of the cases with obstructive jaundice were secondary to malignant diseases (97%), which is in concordance with previous studies. [11][12][13][14][15][16] Only 3 out of the 102 patients presented with benign biliary strictures.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies show pancreatic carcinoma to be the leading cause of biliary obstruction. [11][12][13][14][15][16] A study performed by Sharma et al showed CA gall bladder to be the leading cause of obstructive jaundice. 11 The overall complication rate was 29.4% which is higher than the previously reported 7% by Liu et al 8 Previously, in the local population the overall complication rate was reported as 41% by Haq et al which was markedly higher than the present figure.…”
Section: Discussionmentioning
confidence: 99%
“…Yine aynı çalışmada saptanan, ALP ve WBC yüksekliğinin de mortalite ile ilişkili olma durumu ise bizim çalışmamızda saptanmadı. Bilirübin düzeyi yüksekliğinin mortalite ile ilişkisi olduğuna dair literatürde pek çok çalışma bulunmaktadır(10,21).Hastalarımızın tamamına USG yapıldı ve %88.6'sında USG'nin obtrüksiyonu saptadığı ancak %47.7'sinde USG ile tanı konulabildiği gözlendi. Malign sebeplerin %50.7'sine, benign sebeplerin %45.8'ine USG ile tanı koyuduğu görüldü.…”
unclassified